IMPLEMENTASI PERATURAN BUPATI NO 20 TAHUN 2010 TENTANG KEBIJAKAN PERCEPATAN PENGANEKARAGAMAN KONSUMSI PANGAN BERBASIS SUMBER DAYA LOKAL DI KABUPATEN KUDUS - adhitya nugraha; purwoko .; wiwik widayati (Journal of Politic and Government Studies, 2015)
ABSTRACT Diversification of food consumption is an attempt to cultivate food consumption patterns are diverse and balanced in the amount and composition sufficient to meet nutritional needs. Decree No. 20 Year 2010 on Food Consumption Diversification Acceleration Policy-Based Local Resources in Kudus is one of the government's efforts in implementing food consumption patterns are diverse, nutritious, balanced and safe to the public. In a broad sense the implementation of the policy is a way for a policy can achieve its objectives and bring results, as expected.The research method used in this study the descriptive research method with quantitative-qualitative approach to research that aims to describe and interpret the research object in accordance with the reality, and to develop theories and phenomena are interrelated.In the implementation of the policy of diversification of food consumption based on local resources in Kudus, has been carried out properly and in earnest since 2011 and received an award from the Ministry of Agriculture as one of the 50 districts / cities that have implemented P2KP best version of the Ministry of Agriculture and grown steadily every year, The implementation of the P2KP policies supported by the socialization, coaching, and counseling is done by executing competent, and can not be separated from the support of the people who actively participate in each program. Based on the research, there are obstacles in the implementation process of policy implementation P2KP is the total lack of executive experts, coordination among the implementing competent with implementing a junior less, and the results achieved have not been in line with expectations due to the consumption patterns of grain / rice still dominates, but the decline annually from 2011 to 2014.The implementation of policy implementation accelerated diversification of food consumption based on local resources in Kudus, it can be said that the role and support of the government has been optimal, but changing patterns of food consumption will be grain/rice as a staple food is hard to diverted. Education from an early age to form a pattern of food consumption varied, nutritious, balanced and secure much needed, to form the next generation that understands and memahani diverse patterns of food consumption. Keywords: Policy Implementation, Bupati Regulations, P2KP